Saccharomyces cerevisiae displays a stable transcription start site landscape in multiple conditions. Issue 2 (22nd December 2018) - Börlin, Christoph S; Cvetesic, Nevena; Holland, Petter; Bergenholm, David; Siewers, Verena; Lenhard, Boris; Nielsen, Jens
Abstract: One of the fundamental processes that determine cellular fate is regulation of gene transcription. Understanding these regulatory processes is therefore essential for understanding cellular responses to changes in environmental conditions. At the core promoter, the regulatory region containing the transcription start site (TSS), all inputs regulating transcription are integrated. Here, we used Cap Analysis of Gene Expression (CAGE) to analyze the pattern of TSSs at four different environmental conditions (limited in ethanol, limited in nitrogen, limited in glucose and limited in glucose under anaerobic conditions) using the Saccharomyces cerevisiae strain CEN.PK113–7D. With this experimental setup, we were able to show that the TSS landscape in yeast is stable at different metabolic states of the cell. We also show that the spatial distribution of transcription initiation events, described by the shape index, has a surprisingly strong negative correlation with measured gene expression levels, meaning that genes with higher expression levels tend to have a broader distribution of TSSs. Our analysis supplies a set of high-quality TSS annotations useful for metabolic engineering and synthetic biology approaches in the industrially relevant laboratory strain CEN.PK113–7D, and provides novel insights into yeast TSS dynamics and gene regulation. Abstract : High-quality data set annotating transcription start sites in Saccharomyces cerevisiae reveals a stable transcription start site landscape in different conditions.